Dual Lewis Acidic/Basic Pd0.5Ru0.5–Poly(N‐vinyl‐2‐pyrrolidone) Alloyed Nanoparticle: Outstanding Catalytic Activity and Selectivity in Suzuki–Miyaura Cross‐Coupling Reaction. Issue 23 (5th October 2015) - Kutubi, Md. Shahajahan; Sato, Katsutoshi; Wada, Kenji; Yamamoto, Tomokazu; Matsumura, Syo; Kusada, Kohei; Kobayashi, Hirokazu; Kitagawa , Hiroshi; Nagaoka, Katsutoshi
Abstract: This article anticipates the development of dual Lewis acidic/basic alloyed nanoparticle (NP) of poly( N ‐vinyl‐2‐pyrrolidone)‐stabilized Pd0.5 Ru0.5 solid solution, revealing equivalent Pd δ + and Ru δ − on the NP surface. This unsupported NP disclosed excellent catalytic efficiency with high turnover frequency, 15 000 h −1 in Suzuki–Miyaura cross‐coupling under notable drop of both Pd loading (0.08 mol %) and time (5 min) in air, attributed for its bifunctional acidic/basic modes. The bifunctional modes exposed the most interesting new reaction mechanism ascribed by the inductive effects of p ‐substituents in arylboronic acid, accelerated reactivity by electron‐withdrawing group, revealing an opposite reactivity trend relative to other Pd‐based catalysts. Besides, the significant drops of Pd loading and reaction time impeded the metal leaching associated with no changes in NP surface composition/structure after the 3rd cycle (>99 % efficiency), revealing a line‐up for this NP in the environmental sustainability. Abstract : Opposing charges, working together : Bifunctional Lewis acidic/basic Pd δ + Ru δ − (1:1) solid‐solution nanoparticles disclose a remarkable catalytic efficiency in the Suzuki–Miyaura reaction at very low Pd loading and short reaction time in air. It reveals enhanced reactivity by the electron‐withdrawing groups on arylboronic acids, resulting negatively charged aromatic ring in the transition state, which is a clear controversy to the conventional Pd catalysis.